Sacred Sustenance: A Maudhu’i Inquiry into the Integrated Quranic Paradigm of Consumption - Muhammad Fathur Rozaq (An-Nur International Journal of The Quran & Hadith, 2026)
This study explores the pedagogical architecture of food in the Qur’an through a thematic exegesis (tafsir maudhu‘i) of 55 selected verses. It argues that the Quranic discourse on food transcends simple dietary regulations, forming a systematic ‘alimentary circuit’ designed for moral and spiritual integrity. The research identifies four interconnected dimensions: the Ontological (food as a divine sign), the Normative (legal boundaries of halal-haram), the Axiological (ethics of restraint and social justice), and the Eschatological (consumption as a bridge to the afterlife). Central to this paradigm is the synthesis of Meccan and Medinan revelations. The Meccan phase establishes a theological buffer by anchoring consumption in Rububiyah (Divine Sovereignty), while the Medinan phase provides the legal framework. This study finds that modern consumption often suffers from a "pedagogical rupture," where formal halal labels are detached from their spiritual and ethical roots. By reintegrating these dimensions, the study reconstructs a holistic paradigm of "Sacred Sustenance," where consumption serves as a core vehicle for theological awareness and social equity. Ultimately, the synthesis of Meccan soul-formation and Medinan body-regulation offers a comprehensive framework to address spiritual regression in contemporary food practices.